Prospective, multicenter, randomized phase III trial evaluating the impact of lymphoscintigraphy as part of sentinel node biopsy in early breast cancer: SenSzi (GBG80) Trial - Kümmel, Sherko; Holtschmidt, Johannes Claus; Gerber, Bernd; Assen, Albert von der; Heil, Jörg; Thill, Marc; Krug, David; Schem, Christian; Denkert, Carsten; Lubitz, Juliane; Blohmer, Jens-Uwe; Reinisch, Mattea (Journal of clinical oncology, 2019)
PURPOSEThe aim of the current work was to clarify whether a preoperative lymphoscintigraphy (LSG) enhances staging accuracy of sentinel lymph node biopsy (SLNB).PATIENTS AND METHODSIn a prospective, multicenter, randomized phase III trial, patients with cN0 early breast cancer or extensive/high-grade ductal carcinoma in situ planned for standard radioactive-labeled colloid LSG with subsequent SLNB were randomly assigned 1:1 to receive SLNB either with knowledge of the LSG findings or without. As the false-negative rate of SLNB correlates with the number of resected sentinel lymph nodes (SLNs), our primary end point was the mean number of histologically detected SLNs per patient. One thousand one hundred two evaluable patients were necessary to demonstrate noninferiority of SLNB without LSG. Stratified one-sided 95% CI for the difference (without LSG − with LSG) in the mean number of histologically detected SLNs had to be greater than −0.27 (10% noninferiority margin). Stratification was performed according to tumor focality and trial site. Additional predefined secondary end points (rates of node-positive patients and of completion axillary lymph node dissection) were analyzed to rule out differences in the reliable detection of nodal metastases.RESULTSBetween May 2014 and October 2015, 1,198 patients were randomly assigned in 23 German and Swiss breast centers. Modified intention-to-treat analysis (n = 1,163) showed a mean number of histologically detected SLNs of 2.21 with LSG and 2.26 without LSG (difference 0.05; stratified 95% CI, −0.18 to infinity), thus establishing noninferiority of omitting preoperative LSG. Secondary end points displayed no statistically significant differences.CONCLUSIONWe show that SLNB is equally effective irrespective of the surgeon’s knowledge of preoperative LSG results. SLNB without LSG will speed up the preoperative workflow and reduce cost.